Pathophysiological aspects of transferrin-A potential nano-based drug delivery signaling molecule in therapeutic target for varied diseases - Li, Chang; Zhou, Liya; Yin, Xunzhe (Frontiers in Pharmacology, 2024)
Transferrin (Tf), widely known for its role as an iron-binding protein, exemplifies multitasking in biological processes. The role of Tf in iron metabolism involves both the uptake of iron from Tf by various cells, as well as the endocytosis mediated by the complex of Tf and the transferrin receptor (TfR). The direct conjugation of the therapeutic compound and immunotoxin studies using Tf peptide or anti-Tf receptor antibodies as targeting moieties aims to prolong drug circulation time and augment efficient cellular drug uptake, diminish systemic toxicity, traverse the blood-brain barrier, restrict systemic exposure, overcome multidrug resistance, and enhance therapeutic efficacy with disease specificity. This review primarily discusses the various biological actions of Tf, as well as the development of Tf-targeted nano-based drug delivery systems. The goal is to establish the use of Tf as a disease-targeting component, accentuating the potential therapeutic applications of this protein.